Product Quality and Market Efficiency: The Effect of Product Recalls on Resale Prices and Firm Valuation - Hartman, Raymond S. (The Review of Economics and Statistics, 1987)
Raymond S. Hartman, Product Quality and Market Efficiency: The Effect of Product Recalls on Resale Prices and Firm Valuation, The Review of Economics and Statistics, Vol. 69, No. 2 (May, 1987), pp. 367-372